Numerical analysis of spray characteristics of dimethyl ether and diethyl ether fuel. (1st January 2017) - Mohan, Balaji; Yang, Wenming; Yu, Wenbin; Tay, Kun Lin
Highlights: Thermo-physical properties of liquid DME and DEE are reported. Ether fuels tend to cavitate higher compared to that of diesel fuel. Spray tip penetration and SMD are found to be lesser for ether fuels. Ether fuels shows excellent atomization behavior. Abstract: In this work, the spray characteristics of ether fuels such as dimethyl ether (DME) and diethyl ether (DEE) have been numerically investigated using KIVA-4 CFD code. A new hybrid spray model developed by coupling the standard KHRT model to cavitation sub model was used. The detailed thermo-physical properties of ether fuels have been predicted and validated with experimental results available from literature. The cavitation inception inside the injector nozzle hole has been studied for ether fuels in comparison with diesel fuel. It was found that ether fuels cavitates higher compared to that of conventional diesel fuel because of its low viscosity. The spray tip penetration of diesel fuel was longer than that of ether fuels due to high viscosity and density of diesel fuel. Ether fuels characterized by low Ohnesorge number and high Reynolds number showed better atomization behavior compared to that of the diesel fuel.